Benign hilar bile duct strictures resected as perihilar cholangiocarcinoma. Issue 11 (6th August 2019) - Otsuka, S.; Ebata, T.; Yokoyama, Y.; Igami, T.; Mizuno, T.; Yamaguchi, J.; Onoe, S.; Watanabe, N.; Shimoyama, Y.; Nagino, M.
Abstract : Background: Differentiation between perihilar cholangiocarcinoma (PHCC) and benign strictures is frequently difficult. The aim of this study was to investigate the incidence and long‐term outcome of patients with tumours resected because of suspicion of PHCC, which ultimately turned out to be benign (malignancy masquerade). Methods: Patients who underwent surgical resection with a diagnosis of PHCC between 2001 and 2016 were reviewed retrospectively. Results: Among 707 consecutive patients, 685 had PHCC and the remaining 22 (3·1 per cent) had benign biliary stricture. All patients with benign disease underwent major hepatectomy, with no deaths. Preoperative histological assessment using bile duct biopsy or aspiration cytology had a high specificity (90 per cent), low sensitivity (62 per cent) and unsatisfactory accuracy (63 per cent). Despite the increasing use of histological assessment, the incidence of benign strictures resected did not decrease over time, being 0·9 per cent in 2001–2004, 4·0 per cent in 2005–2008, 3·8 per cent in 2009–2012 and 2·9 per cent in 2013–2016. The final pathology of benign strictures included IgG4‐related sclerosing cholangitis (9 patients), hepatolithiasis (4), granulomatous cholangitis (3), non‐specific chronic cholangitis (3), benign strictures after cholecystectomy (2), and a benign stricture possibly caused by parasitic infection (1). The 10‐year overall survival rate for the 22 patients with benign stricture was 87 per cent, without recurrence of biliary stricture. Conclusion: The incidence of benign strictures resected as PHCC as a proportion of all resections was relatively low, at 3·1 per cent. Currently, unnecessary surgery for suspected PHCC is unavoidable. Abstract : A total of 707 consecutive patients underwent resection following diagnosis of presumed perihilar cholangiocarcinoma; 685 of these patients had cholangiocarcinoma, and the remaining 22 (3·1 per cent) had benign biliary stricture. Despite the increasing use of preoperative histological assessment, the incidence of benign stricture resection was unchanged over time. Does not happen that often Abstract : Antecedentes: La diferenciación entre colangiocarcinoma perihilar ( perihilar colangiocarcinoma, PHCC) y estenosis benignas es con frecuencia difícil. El objetivo de este estudio fue investigar la incidencia y el resultado a largo plazo de los tumores resecados con sospecha diagnóstica de PHCC, que finalmente resultaron ser benignos (malignidad enmascarada). Métodos: Se revisaron retrospectivamente los pacientes con diagnóstico de PHCC que se sometieron a resección quirúrgica entre 2001 y 2016. Resultados: Entre 707 pacientes consecutivos, 685 pacientes presentaban PHCC y los 22 restantes (3, 1%) tenían una estenosis biliar benigna. Todos los pacientes con patología benigna se sometieron a una hepatectomía mayor, sin mortalidad. La evaluación histológica preoperatoria mediante biopsia de conducto biliar o citología por aspiración tuvo una alta especificidad (90%), una baja sensibilidad (62%) y una exactitud diagnóstica insatisfactoria (63%). A pesar del uso creciente de la evaluación histológica, la incidencia de estenosis benignas resecadas no disminuyó con el tiempo, con un 0, 9% en 2001‐2004, un 4, 0% en 2005‐2008, un 3, 8% en 2009‐2012 y un 2, 9% en 2013‐2016. La patología final de las estenosis benignas incluyó colangitis esclerosante relacionada con IgG4 ( n = 9), hepatolitiasis ( n = 4), colangitis granulomatosa ( n = 3), colangitis crónica no específica ( n = 3), estenosis benignas tras una colecistectomía ( n = 2) y una estenosis benigna posiblemente causada por una infección parasitaria ( n = 1). Los resultados a largo plazo de los 22 pacientes con estenosis benigna fueron mejores (tasa de supervivencia a 10 años; 87, 4%) sin recidiva de la estenosis biliar. Conclusión: La incidencia de pacientes con estenosis benignas resecadas como PHCC en comparación con todas las resecciones fue relativamente baja, del 3, 1%. Actualmente, la cirugía "innecesaria" por sospecha de PHCC es inevitable.